Organocopper complexes during roxarsone degradation in wastewater lagoons - Andra, Syam S.; Quazi, Shahida; Sarkar, Dibyendu; Datta, Rupali K.; Bach, Stephan B H; Makris, Konstantinos C. (My University, 2010)
Background, aim, and scope: Organoarsenical-containing animal feeds that promote growth and resistance to parasites are mostly excreted unchanged, ending up in nearby wastewater storage lagoons. Earlier work documented the partial transformation of organoarsenicals, such as, 3-nitro-4-hydroxyphenylarsonic acid (roxarsone) to the more toxic inorganic arsenate [As(V)] and 3-amino-4-hydroxyphenylarsonic acid (3-AHPAA). Unidentified roxarsone metabolites using liquid chromatography coupled to inductively coupled plasma mass spectrometry (LC/ICP-MS) were also inferred from the corresponding As mass balance. Earlier batch experiments in our laboratory suggested the presence of organometallic (Cu) complexes during relevant roxarsone degradation experiments. We hypothesized that organocopper compounds were complexed to roxarsone, mediating its degradation in field-collected swine wastewater samples from storage lagoons. The objective of this study was to investigate the role of organometallic (Cu) complexes during roxarsone degradation under aerobic conditions in swine wastewater suspensions, using electrospray ionization mass spectrometry (ES-MS). Materials and methods: Two swine wastewater samples differing in % solids content and total recoverable Cu concentrations were reacted with 500 ppb of roxarsone under aerobic conditions for 16 days. LC/ICP-MS and ES-MS were used for As speciation analyses, and characterization of metal-organoarsenical complexes in swine wastewater subsamples, respectively. Results and discussion: An organocopper roxarsone metabolite was found only in the high-Cu wastewater sample, suggesting the role of Cu in roxarsone degradation under aerobic conditions. The organocopper metabolite was not found in the low-Cu wastewater sample, because roxarsone did not undergo degradation under aerobic conditions even after 16 days. Conclusions: Aerobic degradation of organoarsenicals (roxarsone) has not been documented before. Preliminary dataset from this study illustrates the direct and/or indirect association of particulate Cu in catalyzing roxarsone degradation under aerobic conditions in samples with high % solids content. Recommendations and perspectives: Concerns regarding the degradation of roxarsone in wastewater to the more toxic inorganic As may be partially linked to the presence of particulate Cu. The presence of Cu in wastewater-suspended particle surfaces has never been coupled before to organoarsenicals degradation reactions, thus, further studies are needed to elucidate the related reaction mechanisms and pathways. Water depth-dependent solid particle distribution profiles in wastewater storage lagoons could provide empirical evidence towards the design of effective degradation practices for nitrophenol-containing compounds, such as, organoarsenical-containing antibiotics, or explosive munitions compounds.
Keywords: Animal waste; Antibiotics; Copper; Degradation; Environmental health; Explosives; Nitrophenols; Organoarsenicals; Remediation